Diversity of Soil Macrofauna Across Different Habitat Types in the Core Area of Batutegi Protected Forest, Tanggamus, Lampung - Master, Jani; Umar, Suratman; Subagio, Aris; Suhandi, Salsabiil M. (Jurnal Biologi Papua, 2025)
Soil macrofauna are important bioindicators of soil fertility. Soil fertility is strongly influenced by soil conditions, which affect the presence and density of macrofauna populations through the decomposition of organic matter. This study aimed to determine the diversity of soil macrofauna across different habitat types in the Batutegi Protection Forest (BPF), Tanggamus, Lampung. The methods used included pitfall traps, point counts, and hand sorting. Three plots were set up, each with three pitfall traps. The point count method involved walking a 100-meter transect with 10 stopping points, each observed for 10 minutes. The hand sorting method was conducted in three 25 × 25 cm plots at a depth of 20 cm. The soil macrofauna diversity indices obtained using the pitfall trap method were as follows: river border (H'=2.9), shrub area (H'=3.1), and forest interior (H'=3.1). Using the point count method, the diversity indices were: river border (H'=3.5), shrub area (H'=2.8), and forest interior (H'=3.3). The diversity indices from the hand sorting method were: river border (H'=2.7), shrub area (H'=2.4), and forest interior (H'=1.8).